Unfolded DapA forms aggregates when diluted into free solution, confounding comparison with folding by the GroEL/GroES chaperonin system. Issue 4 (17th January 2015) - Ambrose, Andrew J.; Fenton, Wayne; Mason, Damian J.; Chapman, Eli; Horwich, Arthur L.
Abstract : A recent hydrogen–deuterium exchange study of folding of the GroEL/GroES‐dependent bacterial enzyme DapA has suggested that the DapA folding pathway when free in solution may differ from the folding pathway used in the presence of the GroEL/GroES chaperonin. Here, we have investigated whether DapA aggregation might be occurring in free solution under the conditions of the exchange experiment, as this would confound interpretation of the pathway predictions. Dynamic light scattering (DLS) data, sedimentation analysis and refolding yield indicate that significant aggregation occurs upon dilution of DapA from denaturant, bringing into question the earlier conclusion that different folding pathways occur in the absence and presence of the chaperonin system. Abstract : DapA diluted into solution produces large light scattering signals. Sedimentation indicates precipitation of ∼25% of DapA when refolded in solution. Yield of DapA refolded in solution is reduced compared to that from GroEL/GroES. Aggregation of DapA confounds interpretation of refolding pathway data.